Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.dadm.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Plasma BDNF levels associate with Pittsburgh Compound B binding in the brain

Abstract: Background Brain-derived neurotrophic factor (BDNF) plays an important role in Alzheimer's disease (AD) and other neurodegenerative disorders. BDNF function is adversely affected by amyloid beta in AD. BDNF levels in brain and peripheral tissues are lower in patients with AD and mild cognitive impairment (MCI) than in controls. Here we examined the association between plasma levels of BDNF and amyloid deposition in the brain measured with Pittsburgh Compound B (PiB). Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
(74 reference statements)
1
16
0
Order By: Relevance
“…More recently, a study carried out in an ADNI-based MCI cohort revealed that plasma IL-6 receptor, clusterin, and ApoE levels coupled with a number of clinical and demographic measures, APOE genotype and mean hippocampal volume, achieved 79 and 83% sensitivity and specificity for prediction of NAB ( 125 ). Hwang et al also reported an association of reduced plasma BDNF levels with increased regional measures of NAB in an ADNI cohort ( 141 ).…”
Section: Discovery Of Blood-based Biomarkers Of Ad Pathology Using Anmentioning
confidence: 94%
See 1 more Smart Citation
“…More recently, a study carried out in an ADNI-based MCI cohort revealed that plasma IL-6 receptor, clusterin, and ApoE levels coupled with a number of clinical and demographic measures, APOE genotype and mean hippocampal volume, achieved 79 and 83% sensitivity and specificity for prediction of NAB ( 125 ). Hwang et al also reported an association of reduced plasma BDNF levels with increased regional measures of NAB in an ADNI cohort ( 141 ).…”
Section: Discovery Of Blood-based Biomarkers Of Ad Pathology Using Anmentioning
confidence: 94%
“…This work replicated an association of two proteins with NAB; pancreatic polypeptide across the cohort of AD, MCI, and cognitively healthy elderly, and IgM in the cognitively healthy elderly group, while the association of the other protein candidates with NAB was not replicated ( 142 ). This lack of replication between studies is disappointing; however, it is quite possible that this could be in part due to technical platform differences, as the discovery studies used both MS ( 137 , 140 ) and immunocapture-based approaches ( 125 , 138 , 139 , 141 ), while replication was sought using the SOMAscan platform ( 142 ). As mentioned earlier, platform and assay differences may provide differing quantitative proteomic results, given that there are key differences in the nature of the protein being measured by these techniques.…”
Section: Discovery Of Blood-based Biomarkers Of Ad Pathology Using Anmentioning
confidence: 99%
“…Moreover, BDNF also can be produced by peripheral blood mononuclear cells (PBMC) in amounts that vary in diverse pathological conditions [17]. Accumulating data suggest that reduced circulating BDNF levels are present in MCI and AD patients and are related to poorer cognition, smaller hippocampal volume, and recently also to widespread brain amyloid burden [18]. …”
Section: Introductionmentioning
confidence: 99%
“…It is highly expressed in brain areas that rely on neuroplasticity, including the hippocampus, hypothalamus, and cortex (Egan et al, 2003). Serum BDNF levels have been shown to provide an indirect reflection of the supply of BDNF in the brain because BDNF crosses the blood-brain barrier (Hwang et al, 2015; Pan, Bandks, Fasold, Bluth, & Kastin, 1998). When compared with healthy adults, persons with Alzheimer disease, age-related cognitive decline (Liu et al, 2015), and schizophrenia (Vinogradov et al, 2009) had lower serum BDNF levels.…”
mentioning
confidence: 99%